2011
DOI: 10.1101/gr.122226.111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of alternative splicing associated with aging and neurodegeneration in the human brain

Abstract: Age is the most important risk factor for neurodegeneration; however, the effects of aging and neurodegeneration on gene expression in the human brain have most often been studied separately. Here, we analyzed changes in transcript levels and alternative splicing in the temporal cortex of individuals of different ages who were cognitively normal, affected by frontotemporal lobar degeneration (FTLD), or affected by Alzheimer's disease (AD). We identified age-related splicing changes in cognitively normal indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
193
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(208 citation statements)
references
References 66 publications
6
193
0
1
Order By: Relevance
“…This trend is evident in both wild‐type mice during physiological aging and in a premature aging mouse model, suggesting that alternative splicing might be more important in the aging process than has previously been noted. Our results are in agreement with those of other recent studies that have shown an effect of age on AS in human brain (Tollervey et al ., 2011; Mazin et al ., 2013), human peripheral blood leukocytes (Harries et al ., 2011), and senescent fibroblasts induced by telomere shortening (Cao et al ., 2011). To our knowledge, this is the first study to show that the amount of age‐related AS increases with more advanced age (4–18 months compared to 4–28 months) and in several tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is evident in both wild‐type mice during physiological aging and in a premature aging mouse model, suggesting that alternative splicing might be more important in the aging process than has previously been noted. Our results are in agreement with those of other recent studies that have shown an effect of age on AS in human brain (Tollervey et al ., 2011; Mazin et al ., 2013), human peripheral blood leukocytes (Harries et al ., 2011), and senescent fibroblasts induced by telomere shortening (Cao et al ., 2011). To our knowledge, this is the first study to show that the amount of age‐related AS increases with more advanced age (4–18 months compared to 4–28 months) and in several tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In this report the ER␤-HnRNP H interaction was enhanced by E2 in young animals but was decreased or unchanged by E2 in aged animals, suggesting that in aged animals the influence of E2 over the actions of an ER␤-HnRNP H complex might be altered. Estrogen receptors have been shown to participate on some level in miRNA processing (68,69) and mRNA splicing (13), and evidence suggests that aging may lead to a global increase in alternative splicing (70). Recent findings demonstrate that ER␤ is differentially spliced depending upon age and E2 treatment (71).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that changes in splicing are part of the transcriptional signature of aging cells (Deschênes & Chabot, 2017; Stegeman & Weake, 2017). Age‐associated changes in alternative splicing have been observed in human brain and in mouse skin, skeletal muscle, bone, thymus, and white adipose tissue (Rodríguez et al, 2016; Tollervey et al, 2011). Splicing is a highly regulated and integral part of proper gene expression; thus, slight perturbations in splicing can lead to altered function and/or expression.…”
Section: Introductionmentioning
confidence: 99%
“…Many splicing factors show age‐related changes in their expression that correlate with changes in alternative splicing during aging (Harries et al, 2011; Lee et al, 2016; Mazin et al, 2013; Rodríguez et al, 2016; Tollervey et al, 2011; Wood, Craig, Li, Merry, & Magalhães, 2013). For example, as many as one‐third of all splicing factors exhibit altered expression with age in human blood (Holly et al, 2013).…”
Section: Introductionmentioning
confidence: 99%